Reconsidering Systemic Fear and the Stock Market: A Reply to Baines and Hager - James McMahon (Review of Capital as Power, 2021)
This article responds to Baines and Hager's recent critique of the capital-as-power model of the stock market. Proposed by Bichler and Nitzan, this model seeks to explain how financial crises are tied to the concept of `systemic fear'. Bichler and Nitzan tested their initial model on US data, finding a strong correlation between capitalist power (as they measure it) and systemic fear. However, when Baines and Hager extended the model to four other countries, they found conflicting results. I respond to Baines and Hager, and argue that they were perhaps too quick to dismiss systemic fear as a useful concept. I re-examine systemic fear in twelve countries, and find that (with a few exceptions), it correlates with capitalist power. These results suggest that the notion of `systemic fear' is useful for studying both capitalist crisis and national diversity in capitalist development.
Keywords: P16; G1; g12; 330; capitalization; capital as power; sabotage; stock market; systemic fear